MODEL PEMBELAJARAN BERBASIS PORTOFOLIO UNTUK MENGEMBANGKAN NILAI-NILAI MUSYAWARAH DI KELAS XI MULTIMEDIA B SMKN 06 - Naiessy Ariskha; Sulistyarini Sulistyarini; Rum Rosyiid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This study aims to investigate the processes of implementing portfolio-based learning models committed by planning, implementing, and assessment. The processes are applied to students of grade XI Multimedia B SMKN 6 Pontianak to develop the values of deliberation in the learning process of Pancasila and citizenship education. This research method was descriptive with qualitative approach. Source of this study were students of SMKN 6 Pontianak and Pancasila and citizenship education subject teacher. Techniques of data collection were in form of observation and interview. The results showed that the students' deliberation values improved and developed highly which were 21 out of 29 students, other 7 students were also in the criteria and the rest student who was in low criteria in learning achievement also experienced the impact positively which the learning outcomes were improving which firstly showed 80.00 and increased up to 83.00. Therefore, portfolio-based learning model has shown results that tend to be positive and also very effective for making students active. This research suggests to apply this model in learning Pancasila education and citizenship to improve students’ learning quality, hardwire their character education as well as the learning application that helps make learning qualitatively fun.  Keywords: Civic Education, Portofolio, Deliberation